E-WALLET UTILIZATION ON INDIVIDUAL USERS: IMPACT ON SOCIAL, ENVIRONMENTAL, AND PSYCHOLOGICAL FACTORS(Study on MSMEs in Palu City) - Sadam, Saddam Fatur Rahman; Zahra, Femilia; Abdullah, Muhammad Ikbal; Karim, Fikry (Accounting Studies and Tax Journal (COUNT), 2025)
The goal of this study is to examine how individual users' use of e-wallets affects three key aspects of MSMEs in Palu City: social, environmental, and psychological. This study assesses the primary factors influencing technology adoption—performance expectations, effort, social influence, and supportive conditions—using the UTAUT model. The results of a quantitative study using a survey with 397 participants indicated that these three factors were significantly impacted by the use of e-wallets. These findings demonstrate how technology innovation can improve financial inclusion, lessen its negative effects on the environment, and give MSME participants convenience and security.